(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The existence of pre-Roman proper names from the NW of the Iberian Peninsula that may be analysed with certainty as Celtic names, of which I will introduce a few examples, must not be interpreted as an argument in favour of the Celticity of Lusitanian. Instead, we should take this as a proof that, besides Celtic, there was a Celtic penetration inWestern regions, very likely at a later time. I propose a type of bilingualism in wide areas of the West of the Iberian Peninsula at the coming of the Romans. This would be a result of the confluence there of different Indo-European linguistic traditions.